Penerapan Model Pembelajaran Berbasis Masalah Untuk Meningkatkan Hasil Belajar Biologi Siswa Kelas VIII MTs Negeri 1 Tuban - Sofiyah, Siti (Balai Diklat Keagamaan Surabaya, 2020)
This study aims to know the description of teacher and student activities in the Biology learning process by applying the Problem Based Learning model in class VIII B of MTs Negeri 1 Tuban on the structure and function of plant tissue and improving student learning outcomes in class VIII B MTs Negeri 1 Tuban. This research was a Classroom Action Research which was conducted in 2 cycles, the stages of each cycle consisting of planning, implementing, observing, and reflecting. The subjects of this study were 32, teacher and all students of class VIII B at MTs Negeri Tuban. The research instrument used was the observation sheet and the test sheet. The observation sheet is used to describe the learning activities carried out by the teacher and student learning activities during the learning process using the Problem Based Learning model while the test is used to measure student learning outcomes after the learning process by applying Problem Based Learning Model. The results of the analysis of teacher activity observation data before CAR = 25 (good), the first cycle obtained an average score = 28 (good), the second cycle increased to 30 (good). The results of the analysis of student activity observation data before CAR = 20 (Enough), the first cycle obtained an average score = 27.5 (good), the second cycle increased to 28.5 (good). The class average before CAR = 72 with 76% classical completeness (not complete), the first cycle the class average value is 78.125 with a percentage of 78.125% classical learning completeness (not complete) in the second cycle increased to a class average of 87, 8 with a percentage of classical learning completeness of 90.63% (complete). It was concluded that the Problem Based Learning model could increase teacher activity and student activity as well as student learning outcomes in class VIII B of MTs Negeri 1 Tuban.